2013
DOI: 10.1002/chem.201203903
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activation of Olefins by Metal Triflates and Triflimides: Application to Fragrance Chemistry

Abstract: Fragrance compounds constitute a wide family of relatively volatile compounds presenting interesting odour properties. Several processes catalysed by metal triflates and triflimides have been recently developed with a view to applications to fragrance chemistry. These reactions, involving the activation of non-activated olefins, mainly involve inter- and intramolecular carbon-carbon, carbon-oxygen and carbon-sulfur bond formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
11

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 131 publications
0
15
0
11
Order By: Relevance
“…As mentioned above (see Table 1, entry 6), the transformation of 1 a into 2 a could be carried out in toluene at 110 °C by using 0.1 mol % [(JohnPhos)AuCl] ( A ) and 10 mol % Cu(OTf) 2 . The Lewis acids displayed in Table 5 were tested in the absence of gold at 110 °C, which showed that Ga(OTf) 3 , Al(OTf) 3 , Bi(OTf) 3 , and especially In(OTf) 3 are potent catalysts (see conversions in parentheses, 12, 16, 38, and 77 % respectively) 3032. On the other hand, at 50 °C, none of these Lewis acids promoted the transformation of 1 a into 2 a .…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above (see Table 1, entry 6), the transformation of 1 a into 2 a could be carried out in toluene at 110 °C by using 0.1 mol % [(JohnPhos)AuCl] ( A ) and 10 mol % Cu(OTf) 2 . The Lewis acids displayed in Table 5 were tested in the absence of gold at 110 °C, which showed that Ga(OTf) 3 , Al(OTf) 3 , Bi(OTf) 3 , and especially In(OTf) 3 are potent catalysts (see conversions in parentheses, 12, 16, 38, and 77 % respectively) 3032. On the other hand, at 50 °C, none of these Lewis acids promoted the transformation of 1 a into 2 a .…”
Section: Resultsmentioning
confidence: 99%
“…Kobayashi and co-workers found that certain Lewis acidic metal triflates (M = Al, Ga, Ln) are stable in aqueous media (Kobayashi and Manabe, 2000 ; Kobayashi et al, 2002 ). Following this, such metal triflates were reported as water-tolerant Lewis acidic catalysts for a range of organic transformations: aldol condensations, Diels-Alder reactions, Friedel-Crafts acylations and alkylations, radical additions, aromatic nitrations and sulfonylations (Lub et al, 2005 ; Coulombel et al, 2009 ; Robertson and Wu, 2010 ; Williams and Lawton, 2010 ; Prakash et al, 2012 ; Lemière and Duñach, 2013 ; Markiton et al, 2018 ). The metal triflate catalysts were active at low concentrations, bearing the promise of cost-effective and efficient processes, but suffered from limitations in solubility.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, our group's research is focused on the development of new catalytic methodologies for the formation of intramolecular carbon–carbon and carbon–oxygen bonds. This chemistry aims for the synthesis of low‐molecular‐weight compounds with a potential utility as flavour and fragrance ingredients . Special attention is hereby given to the scalability, robustness, and operational simplicity of the experimental procedure.…”
Section: Introductionmentioning
confidence: 99%